The Second Azerbaijan Rural Investment Project : Social Analysis for Better Project Design - Schlossar, Sandra; Owen, Dan (World Bank, Washington, DC, 2012)
Under the first Azerbaijan Rural Investment Project (AzRIP), considerable attention was paid to assessing the socioeconomic impacts on, and participation of, marginal groups. Significant improvements in household incomes, access to services, and the participation of women in decision making were demonstrated. The follow-up AzRIP-2 plans to expand the geographic scope and more accurately capture improvements in social capital. One of the key changes in the new project is a number of livelihood pilots to foster rural employment and offer income support services. For the preparation of AzRIP-2, a stand-alone social assessment was commissioned to validate and enhance project design, and investigate additional indicators to track improvements in social capital. Findings from a spring 2011 social assessment were presented to a stakeholder consultation workshop in Baku in April 2011, and indicated the need to: (i) intensify the mobilization, representation, and participation of internally displaced persons (IDPs); (ii) lower the minimum population requirement for community projects; (iii) foster female leadership; and (iv) integrate the identified social capital indicators into the project's monitoring and evaluation framework.